2020
DOI: 10.1042/bst20191110
|View full text |Cite
|
Sign up to set email alerts
|

Cell signaling and cytomegalovirus reactivation: what do Src family kinases have to do with it?

Abstract: Primary infection with human cytomegalovirus (HCMV) is usually asymptomatic and leads to the establishment of lifelong latent infection. A major site of latency are the CD34+ hematopoietic progenitor cells. Importantly, normal cellular differentiation of CD34+ cells to a macrophage or dendritic cell phenotype is concomitant with viral reactivation. Molecular studies of HCMV latency have shown that the latent viral genome is associated with histone proteins and that specific post-translational modifications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 63 publications
(103 reference statements)
2
12
0
Order By: Relevance
“…5 H ). This is possibly because epigenetic modifications such as histone acetylation are closely related to HCMV infection and reactivation [33] , and such modifications also occur during SARS-CoV-2 infection [34] . Megakaryocytes, on the other hand, could release histone-rich platelets to promote clotting [35] , [36] , which may be one of the mechanisms for thrombosis in COVID-19 patients [37] .…”
Section: Resultsmentioning
confidence: 99%
“…5 H ). This is possibly because epigenetic modifications such as histone acetylation are closely related to HCMV infection and reactivation [33] , and such modifications also occur during SARS-CoV-2 infection [34] . Megakaryocytes, on the other hand, could release histone-rich platelets to promote clotting [35] , [36] , which may be one of the mechanisms for thrombosis in COVID-19 patients [37] .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ligation of CD4 expressed on monocytes, by MHC Class II molecules expressed on other cells, promotes differentiation to macrophages ( 54 ) via Src family kinase (SFK), mitogen-activated protein kinase (MAPK) and extracellular signal-regulated kinase (ERK) pathways. Given the importance of these pathways in HCMV reactivation from dendritic cells ( 55 , 56 ) we attempted to investigate whether inhibitors of ERK-MAPK signaling (U0126) and Src Family Kinases (PP2) prevented reactivation in our co-culture model. Unfortunately, treatment of latently infected monocytes with the inhibitors for the 96 hours incubation required for activated CD4+ T cells and M-CSF and IL-1β to trigger expression of IE2 protein was toxic.…”
Section: Resultsmentioning
confidence: 99%
“…This CXCR3-mediated signalling to the monocyte has been shown to result in monocyte differentiation to a mature myeloid population ( 54 ) and is known to involve the ERK-MAPK pathway. Interestingly, the ERK-MAPK signalling pathway is also utilised by the M-CSF receptor ( 68 ) and Src family kinases are also implicated in reactivation of HCMV ( 55 , 56 ). Unfortunately, due to the toxicity of the inhibitors to the ERK-MAPK signalling pathway over the time required to observe reactivation induced by both CD4+ T cell co-culture as well as M-CSF & IL-1β treatment we were not able to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as well as escaping immune recognition, latently infected cells are also safe from current HCMV antivirals, which also only target lytic replication. However, this latent reservoir of virus in undifferentiated myeloid cells can reactivate during myeloid cell differentiation and/or if the latent cell is subject to inflammatory environments [ 80 ].…”
Section: Strategies For Targeting the Latent Hcmv Reservoirmentioning
confidence: 99%